Exploring ChatGPT Usage in Higher Education: Patterns, Perceptions, and Ethical Implications Among University Students - Ahmed, Rashed (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This abstract reflects the key findings and discussions from the study, providing a comprehensive summary of the research focus and its conclusions (Exploring ChatGPT Usage. This study investigates the integration of ChatGPT in higher education, focusing on usage patterns, perceived benefits, and ethical concerns among university students. A survey of over 100 participants reveals a widespread acceptance of ChatGPT as a learning tool, with students reporting enhanced engagement, personalized learning, and better comprehension of complex subjects. Key advantages include instant feedback, adaptable learning styles, and information accessibility. However, the research also highlights significant ethical concerns such as academic dishonesty, potential over-reliance on AI, and data privacy risks. The findings show a high level of acceptability among students, who reported increased engagement, personalized learning, and better knowledge of hard subjects. Instant feedback, information accessibility, and support for different learning styles were among the key benefits. This study explores the growing usage of ChatGPT among university students, analyzing patterns of adoption, perceived benefits, and the ethical concerns surrounding its integration into higher education. Through an online survey involving over 100 students, the research examines how ChatGPT is used for academic purposes, such as research assistance, writing assignments, and exam preparation, as well as non-academic exploration. Findings reveal a high acceptance rate, with students highlighting benefits such as enhanced engagement, personalized learning, instant feedback, and ease in tackling complex subjects. However, ethical challenges, including the risk of plagiarism, academic dishonesty, and concerns about data privacy, are prominent.